Human umbilical cord‐derived mesenchymal stem cells conditioned medium attenuate interstitial fibrosis and stimulate the repair of tubular epithelial cells in an irreversible model of unilateral ureteral obstruction. Issue 8 (29th July 2018) - Liu, Bo; Ding, Feng‐Xia; Liu, Yang; Xiong, Geng; Lin, Tao; He, Da‐Wei; Zhang, Yuan‐Yuan; Zhang, De‐Ying; Wei, Guang‐Hui
Abstract: Aim: The growing number of patients suffering from chronic renal disease (CKD) is a challenge for the development of innovative therapies. Researchers have studied the therapeutic effects of cell therapy in acute kidney injury (AKI). However, the therapeutic effect of conditional medium (CM) in the CKD models have been rarely reported. Here, we examined the effects of umbilical cord derived‐mesenchymal stem cells (hUC‐MSCs) CM on renal fibrosis in a rat model of unilateral ureteral obstruction (UUO). Methods: Animals were randomly divided into three groups: sham‐operated, UUO, UUO + CM. CM was administered via the left renal artery after total ligation of the left ureter. Rats were killed after 14 days of obstruction. Histological changes and oxidative stress parameters were assessed. Western blotting and immunohistochemistry analysis were used to measure epithelial‐mesenchymal transition (EMT) markers, including epithelial cadherin (E‐cadherin), α‐smooth muscle actin (α‐SMA), tumour necrosis factor‐α (TNF‐α), Collagen‐I, and transforming growth factor β1 (TGF‐β1). Proliferation and apoptosis of renal tubular epithelial cells (RTEs) were also measured. Results: HucMSC‐CM significantly reduced the levels of malondialdehyde (MDA) and reactive oxygen species (ROS), and increased the activity of glutathione (GSH) induced by UUO. Moreover, CM significantly reduced the expression of TGF‐β1, α‐SMA, TNF‐α and Collagen‐I in UUO kidney, promoted the proliferation of RTEs and inhibited its apoptosis. In addition, the increased expression of E‐cadherin also reflects the effective improvement of renal interstitial fibrosis. Conclusion: This study shows that CM protects UUO‐induced kidney damage and therefore could be a potential tool to prevent CKD progression. Summary at a Glance: This paper reports the renoprotective effects of conditioned media (CM) from umbilical cord derived‐mesenchymal stem cells using a model of unilateral ureteral obstruction in rats. A variety of indicators of fibrosis were reduced following the administration of CM, together with the concurrent reduction in oxidative stress and increased antioxidant enzymes.